Classification of Browning on Intact Table Grape Bunches Using Near-Infrared Spectroscopy Coupled With Partial Least Squares-Discriminant Analysis and Artificial Neural Networks - Daniels, Andries J.; Poblete-Echeverría, Carlos; Nieuwoudt, Hélène H.; Botha, Nicolene; Opara, Umezuruike Linus (Frontiers in Plant Science, 2021)
Table grape browning is a complex physiological disorder occurring during cold storage. Novel and innovative ways need investigation to manage the problem that hampers progressive and sustainable growth of table grape industries. Given the complex nature of the browning phenomenon, there can be the utilization of a technique such as near-infrared spectroscopy (NIR) for the non-destructive classification of different browning phenotypes. In this study, NIR coupled with partial least squares discriminant analysis (PLS-DA) and artificial neural networks (ANN) were used to classify bunches as either clear or as having chocolate browning and friction browning based on the spectra obtained of intact ‘Regal Seedless’ table grape bunches that were cold-stored over different periods. Friction browning is the circular spots close to the pedicel area that forms when table grape berries move against each other, and chocolate browning is the discoloration, which originates mostly from the stylar-end of the berry, although the whole berry may appear brown in severe instances. Evaluation of the models constructed using PLS-DA was using the classification error rate (CER), specificity and sensitivity and for ANN using the kappa score. The CER for chocolate browning (25%) was better than that of friction browning (46%) for weeks 3 and 4 for both class 0 (absence of browning) and class 1 (presence of browning). Both the specificity and sensitivity of class 0 and class 1 for friction browning were not as good as for chocolate browning. With ANN the testing kappa score to classify table grape bunches as clear or having chocolate browning or friction browning showed that chocolate browning could be classified with the strong agreement during weeks 3 and 4 and weeks 5 and 6 and that friction browning could be classified with the moderate agreement during weeks 3 and 4. These results open up new possibilities for the development of quality checks of packed table grape bunches prior to export. This has a significant impact on the table grape industries for it will now be possible to evaluate bunches non-destructively during packaging to determine the possibility of these browning types being present when reaching the export market.